Taxonomic revision of four terrestrial isopods (Crustacea: Oniscidea) from Mexico - Ilse E. Segura-Zarzosa; Hortencia Obregón-Barboza; Gopal Murugan; Christopher B. Boyko; Gabino A. Rodriguez-Almaraz; Humberto García-Velazco; Alejandro M. Maeda Martínez (Revista Mexicana de Biodiversidad)
As part of a research project on the taxonomy of the woodlice (Oniscidea) of northern Mexico, isopod collections of Mexican academic institutions were examined. For the first time, the main diagnostic morphological traits of 4 native species are documented using SEM micrographs: Alloniscus mirabilis (Stuxberg, 1875) (Alloniscidae) and Littorophiloscia richardsonae (Holmes & Gay, 1909) (Halophilosciidae) from the northern Pacific coast of Baja California, Venezillo apacheus (Mulaik in Mulaik & Mulaik, 1942) (Armadillidae) from northern central Durango, which is also the first record of this species in Mexico, and Porcellio virgatus (Budde-Lund, 1885) (Porcellionidae) from the northeastern states of Nuevo León and Tamaulipas. The first 2 COI haplotypes (mtDNA) for P. virgatus are reported. Bayesian phylogenetic analysis of COI haplotypes placed P. virgatus in a clade with a Porcellio dilatatus haplotype with high support, forming a group with Porcellio scaber.